Flexible battery
By sealing multiple power generation elements into the outer body of the flexible battery and directly connecting the positive electrode and the negative electrode with a sheet-shaped conductive substrate, the problem of large contact resistance in the prior art is solved, and the internal resistance is reduced and the energy density is improved.
Patent Information
- Application Number
- CN202380068229.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-28
- Filing Date
- 2023-09-14
- Publication Date
- 2025-05-02
AI Technical Summary
In the existing flexible batteries, the contact resistance between the electrode active material layer and the current collector sheet is large, which makes it difficult to sufficiently reduce the internal resistance.
A number of power generation elements are enclosed in the outer body. Each power generation element is composed of a positive electrode, an negative electrode and a solid electrolyte layer. The positive electrode and an negative electrode are respectively connected to a sheet-shaped conductive substrate and are directly connected through a current collector to form an internal low-resistance battery structure.
By directly connecting the positive and negative electrodes, the internal resistance is reduced, and the energy density of the battery and the reliability of the electrical connection are improved.
Smart Images

Figure CN119923739A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a flexible battery with reduced internal resistance. Background Art
[0002] In recent years, with the development of portable electronic devices such as mobile phones and notebook personal computers, and the practical application of electric vehicles, there is a demand for small, lightweight, high-capacity, and high-energy-density batteries.
[0003] At present, in lithium batteries that can meet this requirement, especially lithium ion batteries, the positive electrode active material uses lithium-containing composite oxides such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), the negative electrode active material uses graphite, etc., and an organic electrolyte containing an organic solvent and a lithium salt is used as the non-aqueous electrolyte.
[0004] Furthermore, as the application equipment of lithium ion batteries further develops, lithium ion batteries are required to have a longer life, higher capacity, and higher energy density, and lithium ion batteries with longer life, higher capacity, and higher energy density are also required to have high reliability.
[0005] However, the organic electrolyte used in lithium-ion batteries contains an organic solvent as a flammable substance, so when an abnormal situation such as a short circuit occurs in the battery, the organic electrolyte may generate abnormal heat. In addition, with the high energy density of lithium-ion batteries in recent years and the increasing trend of the amount of organic solvent in the organic electrolyte, the reliability of lithium-ion batteries is further required.
[0006] Under the above situation, all-solid lithium batteries (all-solid batteries) that do not use organic solvents are also being studied. All-solid lithium batteries use a molded body of a solid electrolyte that does not use an organic solvent to replace the conventional organic solvent-based electrolyte, and there is no worry about abnormal heating of the solid electrolyte, and they have high reliability.
[0007] In addition, all-solid-state batteries are not only highly safe, but also highly reliable and environmentally resistant, and have a long lifespan. Therefore, they are expected to be maintenance-free batteries that can contribute to social development while also continuously contributing to peace of mind and safety. By providing all-solid-state batteries to society, we can contribute to the realization of Goal 3 (Ensure healthy lives and promote well-being for all at all ages), Goal 7 (Ensure access to affordable, reliable and sustainable modern energy for all), Goal 11 (Achieve inclusive, safe, resilient (risk-resistant) and sustainable cities and human settlements) and Goal 12 (Ensure sustainable production and consumption patterns) among the 17 goals of the Sustainable Development Goals (SDGs) set by the United Nations.
[0008] However, the popularity of wearable devices in recent years has led to the diversification of display devices and power storage devices. In technical fields represented by thin-film displays, flexible light-emitting bodies formed by thin films such as organic electroluminescent elements (OLEDs), and power storage functions in sheet-shaped solar cells, sheet-shaped or film-shaped flexible batteries are required.
[0009] As a battery that can meet such requirements, Patent Document 1 describes the following: a plurality of batteries with a thickness of 1 mm or less are arranged on a flexible substrate, and the positive electrodes and negative electrodes of the plurality of batteries are connected by wiring, thereby forming a flexible thin battery.
[0010] In addition, Patent Document 2 describes a bendable battery module in which a plurality of all-solid batteries are connected by wiring on a bendable substrate.
[0011] However, in the technologies disclosed in Patent Documents 1 and 2, since each unit cell disposed on a base material (substrate) has an outer casing (container), there is a problem that the volume occupied by components not involved in power generation in the entire battery increases, thereby reducing the energy density.
[0012] On the other hand, Patent Document 3 describes a sheet-shaped battery in which a plurality of solid power generation units are arranged in a checkerboard pattern on a sheet having flexibility and current collection function, and the solid power generation unit is composed of a power generation element in which a positive electrode active material, a solid electrolyte, and a negative electrode active material are stacked in layers. That is, the technology described in Patent Document 3 is effective in improving the energy density of the entire battery because each solid power generation unit is not externally mounted.
[0013] Prior art literature
[0014] Patent Literature
[0015] Patent Document 1: Japanese Patent Application Publication No. 2015-15143
[0016] Patent Document 2: International Publication No. 2016 / 092888
[0017] Patent Document 3: Japanese Patent Application Publication No. 2000-195482 Summary of the invention
[0018] Problems to be solved by the invention
[0019] However, as described in Patent Document 3, when the electrode active material layer is in direct contact with the current collector sheet, the contact resistance is large, and therefore there is a problem in that it is difficult to sufficiently reduce the internal resistance of the battery.
[0020] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a flexible battery having reduced internal resistance of the battery.
[0021] Solutions to Solve Problems
[0022] The flexible battery of the present invention is characterized in that a plurality of power generation elements are enclosed in an outer casing, the power generation elements having a positive electrode, a negative electrode, and a solid electrolyte layer arranged between the positive electrode and the negative electrode, the positive electrode having a positive electrode mixture layer and a sheet-like conductive substrate arranged on the surface of the positive electrode mixture layer, the negative electrode having a negative electrode mixture layer and a sheet-like conductive substrate arranged on the surface of the negative electrode mixture layer, the plurality of power generation elements are arranged on a flexible substrate, and each positive electrode is directly connected to a current collector so that the positive electrodes are connected to each other through the current collector, each negative electrode is directly connected to a current collector so that the negative electrodes are directly connected to each other through the current collector, and connection terminals leading to the outside are respectively connected to the current collectors connecting the positive electrodes to each other and the current collectors connecting the negative electrodes to each other.
[0023] Effects of the Invention
[0024] According to the present invention, a flexible battery having reduced internal resistance can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a cross-sectional view schematically showing an example of the flexible battery of the present invention.
[0026] Figure 2 This is a cross-sectional view schematically showing another example of the flexible battery of the present invention.
[0027] Figure 3 This is a cross-sectional view schematically showing another example of the flexible battery of the present invention.
[0028] Figure 4 It is a schematic representation of Figure 3 Cross-sectional view of a flexible battery being bent.
[0029] Figure 5 This is a scanning electron microscope photograph of the surface (the surface of the positive electrode) in an example of a power generating element.
[0030] Figure 6 This is a perspective view schematically showing an example of the flexible battery of the present invention. DETAILED DESCRIPTION
[0031] Figure 1 This is a longitudinal sectional view schematically showing an example of the flexible battery of the present invention. Figure 1The flexible battery 100 shown is configured by enclosing three power generation elements 110 in an outer casing 150. The power generation element 110 includes a positive electrode 120, a negative electrode 130, and a solid electrolyte layer 140 interposed therebetween.
[0032] exist Figure 1 In the flexible battery 100 shown, the outer casing 150 is composed of flexible substrates (hereinafter, sometimes simply referred to as “substrates”) 160 and 170. Three power generation elements 110 are arranged on the substrates 160 and 170.
[0033] The substrate 160 has an insulating layer 161 and a conductive layer 162, and the conductive layer 162 functions as a collector on the positive electrode side. That is, each positive electrode 120 of the three power generation elements 110 is directly in contact with the conductive layer 162 of the substrate 160, so that the positive electrodes 120 of the three power generation elements 110 are directly connected to each other through the conductive layer 162 as a collector. In addition, a connection terminal 180 for connecting the positive electrode of the flexible battery 100 to an external device is connected to the conductive layer 162.
[0034] In addition, the substrate 170 has an insulating layer 171 and a conductive layer 172, and the conductive layer 172 functions as a collector on the negative electrode side. That is, each negative electrode 130 of the three power generation elements 110 is directly in contact with the conductive layer 172 of the substrate 170, so that the negative electrodes 130 of the three power generation elements 110 are directly connected to each other through the conductive layer 172 as a collector. In addition, a connection terminal 190 for connecting the negative electrode of the flexible battery 100 to an external device is connected to the conductive layer 172.
[0035] In the flexible battery of the present invention, Figure 1 As shown, there are a plurality of power generation elements, which are not separately packaged externally, but are sealed in an external package in the following state: arranged on a flexible substrate, the positive electrode of each power generation element is directly connected to a collector (a collector for connecting positive electrodes to each other), so that all positive electrodes are connected through the collector, and the negative electrode of each power generation element is directly connected to a collector (a collector for connecting negative electrodes to each other), so that all negative electrodes are connected through the collector. Therefore, compared with a battery in which each power generation element (unit cell) is separately packaged externally, the flexible battery of the present invention can reduce the volume ratio of the external package in the whole, so that the energy density can be improved.
[0036] In addition, Figure 1In the flexible battery 100 shown, the positive electrode 120 includes a positive electrode mixture layer 121 and a porous metal substrate 122 as a conductive substrate, and the entirety of the end of the porous metal substrate 122 on the positive electrode mixture layer 121 side is buried in the surface layer of the positive electrode mixture layer 121. That is, the entire area where the porous metal substrate 122 exists corresponds to the area where the positive electrode mixture layer and the porous metal substrate coexist. Furthermore, in the positive electrode 120, the end of the porous metal substrate 122 on the opposite side to the positive electrode mixture layer 121 side ( Figure 1 It should be noted that the dotted line in the positive electrode 120 represents the boundary between the region in the positive electrode mixture layer 121 where the porous metal substrate does not coexist and the region where the positive electrode mixture layer and the porous metal substrate coexist, which is equivalent to the end of the porous metal substrate 122 on the positive electrode mixture layer 121 side.
[0037] Furthermore, in Figure 1 In the flexible battery 100 shown, the negative electrode 130 includes a negative electrode mixture layer 131 and a porous metal substrate 132 as a conductive substrate, and the entirety of the porous metal substrate 132 including the end portion on the negative electrode mixture layer 131 side is buried in the surface layer of the negative electrode mixture layer 131. That is, the entire portion where the porous metal substrate 132 exists corresponds to the region where the negative electrode mixture layer and the porous metal substrate coexist. Furthermore, in the negative electrode 130, the end portion ( Figure 1 It should be noted that the dotted line in the negative electrode 130 represents the boundary between the region in the negative electrode mixture layer 131 where the porous metal substrate does not coexist and the region where the negative electrode mixture layer and the porous metal substrate coexist, which is equivalent to the end of the porous metal substrate 132 on the negative electrode mixture layer 131 side.
[0038] In flexible batteries, such as Figure 1 As shown, the positive electrode includes a positive electrode mixture layer and a sheet-like conductive substrate disposed on the surface of the positive electrode mixture layer, and the negative electrode includes a negative electrode mixture layer and a sheet-like conductive substrate disposed on the surface of the negative electrode mixture layer.
[0039] In a battery (battery module) having a plurality of power generation elements (unit cells), regarding the electrical connection between the power generation elements, when the electrodes of the power generation elements are directly connected to each other via a current collector as in patent document 3, the electrical connection between the positive electrodes and the electrical connection between the negative electrodes tend to become unstable, compared to a method in which the respective power generation elements are housed in an outer casing with the positive and negative connection terminals exposed to the outside and are connected to each other in this state as in patent documents 1 and 2.
[0040] However, in the case where the positive electrode of the power generation element has a positive electrode mixture layer and a sheet-like conductive substrate disposed on the surface of the positive electrode mixture layer, the electrical connection between the sheet-like conductive substrate that functions as a collector of the positive electrode in the power generation element and the positive electrode mixture layer, and the electrical connection between the sheet-like conductive substrate and the collector that connects the positive electrodes to each other can be made good. In addition, in the case where the negative electrode of the power generation element has a negative electrode mixture layer and a sheet-like conductive substrate disposed on the surface of the negative electrode mixture layer, the electrical connection between the sheet-like conductive substrate that functions as a collector of the negative electrode in the power generation element and the negative electrode mixture layer, and the electrical connection between the sheet-like conductive substrate and the collector that connects the negative electrodes to each other can be made good. Therefore, even if each power generation element is not individually externalized, the electrical connection between the power generation elements can be made good, so a flexible battery with higher reliability of electrical connection and low internal resistance can be made.
[0041] Especially in flexible batteries, such as Figure 1 As shown, the positive electrode preferably has a sheet-shaped porous metal substrate as the above-mentioned conductive substrate, at least a portion of the porous metal substrate of the positive electrode, including the end portion on the positive electrode mixture layer side, is buried in the surface portion of the positive electrode mixture layer and is integrated with the positive electrode mixture layer, and the other end portion of the porous metal substrate of the positive electrode is exposed on the surface of the positive electrode. In addition, the negative electrode preferably has a sheet-shaped porous metal substrate as the above-mentioned conductive substrate, at least a portion of the porous metal substrate of the negative electrode, including the end portion on the negative electrode mixture layer side, is buried in the surface portion of the negative electrode mixture layer and is integrated with the negative electrode mixture layer, and the other end portion of the porous metal substrate of the negative electrode is exposed on the surface of the negative electrode. In this case, the electrical connection between the sheet-like porous metal substrate that functions as the collector of the positive electrode in the power generation element and the positive electrode mixture layer, and the electrical connection between the sheet-like porous metal substrate and the collector that connects the positive electrodes to each other can be made better, and the electrical connection between the sheet-like porous metal substrate that functions as the collector of the negative electrode in the power generation element and the negative electrode mixture layer, and the electrical connection between the sheet-like porous metal substrate and the collector that connects the negative electrodes to each other can be made better, thereby further reducing the internal resistance of the flexible battery.
[0042] In addition, Figure 1 In the flexible battery 100 shown, an insulator 200 is arranged between the power generation elements 110, on the left side of the power generation element 110 arranged at the left end in the figure, and on the right side of the power generation element 110 arranged at the right end in the figure. In this way, in the flexible battery, it is preferable to arrange an insulator in at least a part of the region of the flexible substrate where the power generation element is not arranged. Thereby, when the flexible battery is manufactured and used, the positional displacement of the power generation element and the occurrence of a short circuit caused by the contact between the collector on the positive electrode side and the collector on the negative electrode side can be well suppressed.
[0043] Figure 2 A cross-sectional view schematically showing another example of the flexible battery of the present invention is shown. Figure 2 The flexible battery 101 shown in the figure has three power generation elements 110 and is folded in a region where the power generation elements 110 are not arranged. The flexible battery of the present invention can also be folded by adjusting the shape of the outer casing and the insulator arranged in the region where the power generation elements are not arranged. Figure 2 Fold as shown.
[0044] in addition, Figure 3 and Figure 4 A cross-sectional view schematically showing another example of the flexible battery of the present invention is shown. Figure 3 The flexible battery 102 shown has three power generation elements 110 and is connected to Figure 1 Similarly to the flexible battery 100 shown in the figure, an insulator 200 is arranged between the power generation elements 110, on the left side of the power generation element 110 arranged at the left end in the figure, and on the right side of the power generation element 110 arranged at the right end in the figure. In addition, in the flexible battery 102, the thickness (the length in the vertical direction in the figure) of the portion where the insulator 200 is arranged is smaller than the thickness of the portion where the power generation element 110 is arranged. Therefore, the flexible battery 102 is different from, for example, Figure 1 Compared with the flexible battery 100 shown in FIG. Figure 4 As shown, the portion where the insulator 200 is disposed between the power generating elements 110 is bent.
[0045] The flexible battery of the present invention is flexible, for example, Figure 2 The term "flexible" as used in this specification means that the battery can be wound around a core having an outer diameter of 3 mm and bent by more than 90 degrees, and that even when charged and discharged in a bent state, the discharge capacity at a discharge current of 0.2C does not decrease by more than 3% compared to a state in which the battery is not bent (in the flexible battery of the examples described later, it was confirmed that the characteristics described here are satisfied).
[0046] The flexible battery will be described in detail below.
[0047] <Power generation element>
[0048] The power generating element has a positive electrode, a negative electrode, and a solid electrolyte layer interposed therebetween.
[0049] (positive electrode)
[0050] The positive electrode includes a positive electrode mixture layer containing a positive electrode active material and the like, and a sheet-shaped porous metal substrate functioning as a current collector.
[0051] When the flexible battery is a primary battery, the positive electrode active material can be the same as the positive electrode active material used in the non-aqueous electrolyte primary battery known in the past. Specifically, for example, manganese dioxide, lithium-containing manganese oxides [for example, LiMn3O6, composite oxides having the same crystal structure as manganese dioxide (β-type, γ-type, or a structure in which β-type and γ-type are mixed, etc.) and a Li content of 3.5% by mass or less, preferably 2% by mass or less, more preferably 1.5% by mass or less, and particularly preferably 1% by mass or less, etc.], Li a Ti 5 / 3 Lithium-containing composite oxides such as O4 (4 / 3≤a<7 / 3); vanadium oxides; niobium oxides; titanium oxides; sulfides such as iron disulfide; graphite fluoride; silver sulfides such as Ag2S; nickel oxides such as NiO2, etc.
[0052] In addition, when the flexible battery is used as the positive electrode of the secondary battery, the positive electrode active material can be the same as the positive electrode active material used in the conventionally known non-aqueous electrolyte secondary battery. Specifically, Li 1-x M r Mn 2-r O4 (wherein M is at least one element selected from the group consisting of Li, Na, K, B, Mg, Ca, Sr, Ba, Ti, V, Cr, Zr, Fe, Co, Ni, Cu, Zn, Al, Sn, Sb, In, Nb, Ta, Mo, W, Y, Ru and Rh, 0≤x≤1, 0≤r≤1) represented by a spinel lithium manganese composite oxide, Li r Mn (1-s-t) Ni s M t O (2-u) F v (wherein M is at least one element selected from the group consisting of Co, Mg, Al, B, Ti, V, Cr, Fe, Cu, Zn, Zr, Mo, Sn, Ca, Sr and W, 0≤r≤1.2, 0<s<0.5, 0≤t≤0.5, u+v<1, -0.1≤u≤0.2, 0≤v≤0.1) a layered compound represented by 1-x Co 1-r M r Lithium cobalt composite oxide represented by O2 (wherein M is at least one element selected from the group consisting of Al, Mg, Ti, V, Cr, Zr, Fe, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb and Ba, 0≤x≤1, 0≤r≤0.5), Li 1-x Ni 1-r M rLithium nickel composite oxide represented by O2 (wherein M is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Fe, Co, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb and Ba, 0≤x≤1, 0≤r≤0.5), Li 1+s-x M 1-r N r PO4F s (wherein M is at least one element selected from the group consisting of Fe, Mn and Co, N is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb, V and Ba, 0≤x≤1, 0≤r≤0.5, 0≤s≤1) represented by an olivine-type composite oxide, Li 2-x M 1-r N r Pyrophosphate compounds represented by P2O7 (wherein M is at least one element selected from the group consisting of Fe, Mn and Co, N is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb, V and Ba, 0≤x≤2, 0≤r≤0.5), etc., may be used alone or in combination of two or more.
[0053] In the case where the flexible battery is a secondary battery, the average particle size of the positive electrode active material is preferably 1 μm or more, more preferably 2 μm or more, and preferably 10 μm or less, more preferably 8 μm or less. In addition, the positive electrode active material may be a primary particle or a secondary particle formed by agglomeration of primary particles. If a positive electrode active material having an average particle size in the above range is used, the interface with the solid electrolyte contained in the positive electrode increases, so the output characteristics of the battery are further improved.
[0054] The average particle size of various particles (positive electrode active material, solid electrolyte, etc.) referred to in this specification refers to the value of 50% diameter (D) in the cumulative fraction based on volume when the integrated volume is obtained from particles with a small particle size using a particle size distribution measuring device (Microtrac particle size distribution measuring device "HRA9320" manufactured by Nikkiso Co., Ltd., etc.). 50 ).
[0055] When the flexible battery is a secondary battery, the positive electrode active material preferably has a reaction inhibition layer on its surface for inhibiting the reaction with the solid electrolyte contained in the positive electrode.
[0056] In the positive electrode mixture layer, if the positive electrode active material is in direct contact with the solid electrolyte, the solid electrolyte is oxidized to form a resistance layer, and the ion conductivity in the positive electrode mixture layer may be reduced. By providing a reaction inhibition layer that inhibits the reaction with the solid electrolyte on the surface of the positive electrode active material, direct contact between the positive electrode active material and the solid electrolyte is prevented, and the reduction of ion conductivity in the positive electrode mixture layer caused by oxidation of the solid electrolyte can be suppressed.
[0057] The reaction inhibition layer can be made of a material having ion conductivity and capable of inhibiting the reaction between the positive electrode active material and the solid electrolyte. As a material capable of constituting the reaction inhibition layer, for example, an oxide containing Li and at least one element selected from the group consisting of Nb, P, B, Si, Ge, Ti and Zr can be cited, and more specifically, Nb-containing oxides such as LiNbO3, Li3PO4, Li3BO3, Li4SiO4, Li4GeO4, LiTiO3, LiZrO3, Li2WO4, etc. can be cited. The reaction inhibition layer can contain only one of these oxides, or more than two, and further, a plurality of these oxides can also form a composite compound. Among these oxides, Nb-containing oxides are preferably used, and LiNbO3 is more preferably used.
[0058] The reaction suppression layer is preferably present on the surface in an amount of 0.1 to 1.0 parts by mass relative to 100 parts by mass of the positive electrode active material. Within this range, the reaction between the positive electrode active material and the solid electrolyte can be suppressed well.
[0059] Examples of a method for forming a reaction suppression layer on the surface of a positive electrode active material include a sol-gel method, a mechanofusion method, a CVD method, a PVD method, and an ALD method.
[0060] From the viewpoint of further increasing the energy density of the flexible battery, the content of the positive electrode active material in the positive electrode mixture is preferably 60 to 85% by mass.
[0061] The positive electrode mixture may contain a conductive aid. As a specific example, carbon materials such as graphite (natural graphite, artificial graphite), graphene, carbon black, carbon nanofibers, and carbon nanotubes can be cited. It should be noted that, for example, when Ag2S is used as the active material, Ag with conductivity will be generated during the discharge reaction, so it is not necessary to contain a conductive aid. When the positive electrode mixture contains a conductive aid, when the content of the positive electrode active material is set to 100 parts by mass, its content is preferably more than 1.0 parts by mass, preferably less than 7.0 parts by mass, and more preferably less than 6.5 parts by mass.
[0062] In addition, the positive electrode mixture may contain a binder. As a specific example, fluororesins such as polyvinylidene fluoride (PVDF) can be cited. It should be noted that, for example, as in the case where a sulfide-based solid electrolyte is contained in the positive electrode mixture (details are described later), in the case where good formability can be ensured when forming the positive electrode mixture layer even without using a binder, the positive electrode mixture may not contain a binder.
[0063] In the positive electrode mixture, when a binder is required, its content is preferably 15% by mass or less, and preferably 0.5% by mass or more. On the other hand, in the positive electrode mixture, when formability can be obtained even without a binder, its content is preferably 0.5% by mass or less, more preferably 0.3% by mass or less, and further preferably 0% by mass (i.e., without a binder).
[0064] The positive electrode mixture preferably contains a solid electrolyte.
[0065] The solid electrolyte contained in the positive electrode mixture is not particularly limited as long as it has lithium ion conductivity, and for example, a sulfide-based solid electrolyte, a hydride-based solid electrolyte, a halide-based solid electrolyte, an oxide-based solid electrolyte, etc. can be used.
[0066] As sulfide-based solid electrolytes, particles of Li2S-P2S5, Li2S-SiS2, Li2S-P2S5-GeS2, Li2S-B2S3 glass, etc. can be cited. In addition, thio-LISICON-type solid electrolytes (Li 10 GeP2S 12 , Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 Wait 12-12a-b+c+6d- e M 1 3+a-b-c-d M 2 b M 3 c M 4 d M 5 12-e X e (Among them, M 1 Si, Ge or Sn, M 2 P or V, M 3 Al, Ga, Y or Sb, M 4 Zn, Ca or Ba, M 5 is S, or S and O, X is F, Cl, Br or I, 0≤ a < 3, 0 ≤ b + c + d ≤ 3, 0 ≤ e ≤ 3), a solid electrolyte having a thiogermanate crystal structure.
[0067] As the hydride-based solid electrolyte, for example, LiBH4, a solid solution of LiBH4 and the following alkali metal compounds (for example, a solid solution with a molar ratio of LiBH4 to the alkali metal compound of 1:1 to 20:1), etc. can be cited. As the alkali metal compound in the above solid solution, at least one selected from the group consisting of lithium halides (LiI, LiBr, LiF, LiCl, etc.), rubidium halides (RbI, RbBr, RbF, RbCl, etc.), cesium halides (CsI, CsBr, CsF, CsCl, etc.), lithium amide, rubidium amide, and cesium amide can be cited.
[0068] As the halide-based solid electrolyte, for example, monoclinic LiAlCl4, LiInBr4 having a defective spinel structure or a layered structure, monoclinic Li 6-3m Y m X6 (where 0 < m < 2 and X = Cl or Br), etc. In addition, for example, known substances described in International Publication No. 2020 / 070958 and International Publication No. 2020 / 070955 can be used.
[0069] As the oxide-based solid electrolyte, for example, garnet-type Li7La3Zr2O 12 , NASICON-type Li 1+O Al 1+ O Ti 2-O (PO4)3, Li 1+p Al 1+p Ge 2-p (PO4)3, perovskite-type Li 3q La 2 / 3-q TiO3, etc.
[0070] Among these solid electrolytes, from the viewpoint of high lithium ion conductivity, sulfide-based solid electrolytes are preferred, and sulfide-based solid electrolytes containing Li and P are more preferred. From the viewpoints of even higher lithium ion conductivity and high chemical stability, sulfide-based solid electrolytes having a thiogermanate crystal structure are further preferred.
[0071] As the sulfide-based solid electrolyte having a thiogermanate crystal structure, for example, substances represented by the following general formula (1), the following general formula (2), or the following general formula (3), such as Li6PS5Cl, are particularly preferred.
[0072] Li7-k PS 6-k X k (1)
[0073] In the above general formula (1), X represents one or more halogen elements, and 0.2 < k < 2.0 or 0.2 < k < 1.8.
[0074] Li 7-x+y PS 6-x Cl x+y (2)
[0075] In the above general formula (2), 0.05 ≤ y ≤ 0.9, -3.0x + 1.8 ≤ y ≤ -3.0x + 5.7.
[0076] Li 7-a PS 6-a Cl b Br c (3)
[0077] In the above general formula (3), a = b + c, 0 < a ≤ 1.8, 0.1 ≤ b / c ≤ 10.0.
[0078] From the viewpoint of reducing the grain boundary resistance, the average particle size of the solid electrolyte is preferably 0.1 μm or more, more preferably 0.2 μm or more. On the other hand, from the viewpoint of forming a sufficient contact interface between the active material and the solid electrolyte, it is preferably 10 μm or less, more preferably 5 μm or less.
[0079] From the viewpoint of further improving the ionic conductivity in the positive electrode and further improving the output characteristics of the flexible battery, when the content of the positive electrode active material is 100 parts by mass, the content of the solid electrolyte in the positive electrode mixture is preferably 10 parts by mass or more, more preferably 15 parts by mass or more. However, if the amount of the solid electrolyte in the positive electrode mixture is too large, the amount of other components will decrease, and the effects brought by them may become smaller. Therefore, when the content of the positive electrode active material is 100 parts by mass, the content of the solid electrolyte in the positive electrode mixture is preferably 65 parts by mass or less, more preferably 60 parts by mass or less.
[0080] The sheet-like conductive substrate in the positive electrode can use a porous metal substrate, a carbon sheet, etc. As the porous metal substrate, a foamed metal porous body is preferably used. As a specific example of a foamed metal porous body, "Celmet (registered trademark)" of Sumitomo Electric Industries, Ltd. can be cited. It should be noted that the thickness of such a porous metal substrate before being used for the positive electrode (power generation element) is usually greater than the above thickness (thickness in the positive electrode) (for example, the thickness before being compressed is preferably 0.1 mm or more, more preferably 0.3 mm or more, particularly preferably 0.5 mm or more, on the other hand, preferably 3 mm or less, more preferably 2 mm or less, particularly preferably 1.5 mm or less), when the power generation element described later is manufactured, it is compressed in the thickness direction, and its thickness becomes a value described later.
[0081] In order to easily fill the positive electrode mixture into the pores of the porous metal substrate and easily integrate the porous metal substrate and the positive electrode mixture layer in the process of pressurizing the porous metal substrate and the positive electrode mixture, the porosity of the porous metal substrate before being compressed is preferably 80% or more, more preferably 90% or more, and particularly preferably 95% or more. On the other hand, in order to increase the conductivity by making the amount of the substrate above a certain level, the porosity is preferably 99.5% or less, more preferably 99% or less, and particularly preferably 98.5% or less.
[0082] In the positive electrode, from the viewpoint of more reliably integrating the porous metal substrate and the positive electrode mixture layer, the thickness of the portion of the porous metal substrate buried in the positive electrode mixture layer is preferably greater than 10% of the thickness of the porous metal substrate (the thickness of the entire porous metal substrate, including the thickness of the portion where the positive electrode mixture layer coexists. Unless otherwise specified, the thickness of the porous metal substrate shall apply the same below), and more preferably greater than 20%.
[0083] In addition, in the positive electrode, in order to reduce the resistance when contacting with the collector used to connect the positive electrodes of multiple power generation elements to each other, it is preferred that the end of the porous metal substrate on the opposite side of the positive electrode mixture layer is not buried in the positive electrode mixture layer, and the end of the positive electrode (the surface of the positive electrode) is only composed of the porous metal substrate. That is, when the porous metal substrate is compressed in the thickness direction during the manufacture of the power generation element described later, it is preferred that the pores at the end of the porous metal substrate are flattened and disappear, and only the porous metal substrate is exposed on the surface of the positive electrode. However, a part of the pores at the end of the porous metal substrate may not be flattened, and may be filled with a positive electrode mixture, or a part of the positive electrode mixture may be exposed on the surface of the positive electrode together with the end of the porous metal substrate within a range that does not have a significant impact on the contact resistance with the above-mentioned collector.
[0084] Figure 5A scanning electron microscope (SEM) photograph of the surface of an example of a positive electrode is shown. Figure 5 In the illustrated positive electrode, the end of the porous metal substrate 122 is exposed on the surface, but part of the positive electrode mixture 121 a also enters the pores existing at the end of the porous metal substrate and is exposed on the surface of the positive electrode.
[0085] However, the larger the proportion (area ratio) of the positive electrode mixture exposed on the surface of the positive electrode, the greater the contact resistance between the porous metal substrate and the collector used to connect the positive electrodes of multiple power generation elements to each other. Therefore, the proportion of the area of the exposed positive electrode mixture in the positive electrode surface is preferably less than 50% when viewed from above, more preferably less than 25%, further preferably less than 15%, and particularly preferably less than 10%.
[0086] In the positive electrode, when at least a portion of the porous metal substrate is buried in the surface layer of the positive electrode mixture layer, from the viewpoint of more reliably integrating the porous metal substrate and the positive electrode mixture layer, the thickness of the porous metal substrate is preferably 1% or more of the thickness of the entire positive electrode mixture layer (including the thickness of the portion coexisting with the porous metal substrate, unless otherwise specified, the "thickness of the positive electrode mixture layer" referred to below refers to the "thickness of the entire positive electrode mixture layer" referred to herein), more preferably 2% or more, and particularly preferably 3% or more. In addition, from the viewpoint of improving the filling property of the positive electrode mixture layer in the positive electrode, the thickness of the porous metal substrate is preferably less than 30% of the thickness of the positive electrode mixture layer, more preferably less than 20%, and particularly preferably less than 10%.
[0087] It should be noted that in the positive electrode, the thickness of the porous metal substrate is preferably 10 μm or more, more preferably 20 μm or more, particularly preferably 30 μm or more, on the other hand, preferably 300 μm or less, more preferably 200 μm or less, particularly preferably 100 μm or less. In addition, the thickness of the positive electrode mixture layer is preferably 0.2 mm or more, more preferably 0.4 mm or more, particularly preferably 0.6 mm or more, on the other hand, preferably 2 mm or less, more preferably 1.7 mm or less, particularly preferably 1.5 mm or less.
[0088] The thickness of the porous metal substrate, the thickness of the positive electrode mixture layer, and the thickness of the negative electrode mixture layer described later in this specification are respectively obtained by observing the cross section of the thickness direction of the positive electrode or the negative electrode using SEM at a magnification of 50 to 1000 times to find the maximum value of the width in the thickness direction of the area where the porous metal substrate can be confirmed and the area where the positive electrode mixture or the negative electrode mixture can be confirmed. In addition, the thickness of the portion of the porous metal substrate buried in the positive electrode mixture layer or the negative electrode mixture layer is obtained by finding the maximum value of the width in the thickness direction of the portion where the area where the porous metal substrate can be confirmed overlaps with the area where the positive electrode mixture can be confirmed or the area where the negative electrode mixture can be confirmed (the values in the embodiments described later are obtained by these methods).
[0089] In addition, the proportion of the positive electrode mixture exposed on the surface of the positive electrode (area ratio) and the proportion of the negative electrode mixture exposed on the surface of the negative electrode (area ratio) are calculated by the ratio (A / B) of the sum A of the areas of the exposed portions of the positive electrode mixture or the negative electrode mixture in the image obtained by observing the surface of the positive electrode or the negative electrode using SEM at a magnification of 50 to 200 times to the area B of the entire positive electrode or the negative electrode (the values in the examples described later are calculated by this method).
[0090] (negative electrode)
[0091] The negative electrode includes a negative electrode mixture layer containing a negative electrode active material and the like, and a sheet-like porous metal substrate functioning as a current collector.
[0092] As the negative electrode active material, for example, carbon materials such as graphite, lithium titanium oxide (lithium titanate, etc.), simple substances containing elements such as Si and Sn, compounds (oxides, etc.) and alloys thereof, etc. In addition, lithium metal and lithium alloys (lithium-aluminum alloys, lithium-indium alloys, etc.) can also be used as negative electrode active materials.
[0093] From the viewpoint of further increasing the energy density of the battery, the content of the negative electrode active material in the negative electrode mixture is preferably 40 to 80% by mass.
[0094] The negative electrode mixture may contain a conductive aid. As a specific example, the same conductive aid as the material that can be contained in the positive electrode mixture and exemplified above can be cited. When the content of the negative electrode active material is set to 100 parts by mass, the content of the conductive aid in the negative electrode mixture is preferably 10 to 30 parts by mass.
[0095] In addition, the negative electrode mixture may contain a binder. As a specific example, the same substance as the binder exemplified above as a substance that can be contained in the positive electrode mixture can be cited. It should be noted that, for example, as in the case where a sulfide-based solid electrolyte is contained in the negative electrode mixture (described later), in the case where good formability can be ensured when forming the negative electrode mixture layer even without using a binder, the negative electrode mixture may not contain a binder.
[0096] In the negative electrode mixture, when a binder is required, its content is preferably 15% by mass or less, and preferably 0.5% by mass or more. On the other hand, in the negative electrode mixture, when moldability can be obtained even without a binder, its content is preferably 0.5% by mass or less, more preferably 0.3% by mass or less, and further preferably 0% by mass (i.e., no binder is contained).
[0097] The negative electrode mixture preferably contains a solid electrolyte. As a specific example, the same substance as the solid electrolyte exemplified above as a substance that can be contained in the positive electrode mixture can be cited. Among the solid electrolytes exemplified above, from the perspective of high lithium ion conductivity and the function of improving the formability of the negative electrode mixture, it is preferred to use a sulfide-based solid electrolyte, and it is more preferred to use a sulfide-based solid electrolyte having a argyrodite-type crystal structure, and it is further preferred to use a solid electrolyte represented by the above-mentioned composition formula (1), the above-mentioned composition formula (2) or the above-mentioned composition formula (3).
[0098] For the same reasons as in the case of the positive electrode mixture, the average particle size of the solid electrolyte in the negative electrode mixture is preferably 0.1 μm or more, more preferably 0.2 μm or more, and is preferably 10 μm or less, more preferably 5 μm or less.
[0099] From the viewpoint of further improving the ion conductivity in the negative electrode and further improving the output characteristics of the flexible battery, when the content of the negative electrode active material is set to 100 parts by mass, the content of the solid electrolyte in the negative electrode mixture is preferably 30 parts by mass or more, and more preferably 35 parts by mass or more. However, if the amount of solid electrolyte in the negative electrode mixture is too much, the amount of other components decreases, and the effects brought by them may become smaller. Therefore, when the content of the negative electrode active material is set to 100 parts by mass, the content of the solid electrolyte in the negative electrode mixture is preferably 130 parts by mass or less, and more preferably 110 parts by mass or less.
[0100] The sheet-like conductive substrate in the negative electrode can use a porous metal substrate, a carbon sheet, etc. in the same manner as the positive electrode. As the porous metal substrate, a foamed metal porous body is preferably used. As a specific example of a foamed metal porous body, "Celmet (registered trademark)" of Sumitomo Electric Industries, Ltd. can be cited. It should be noted that the thickness of such a porous metal substrate before being used in the negative electrode (power generation element) is usually greater than the above thickness (thickness in the negative electrode) (for example, the thickness before being compressed is preferably 0.1 mm or more, more preferably 0.3 mm or more, particularly preferably 0.5 mm or more, on the other hand, preferably 3 mm or less, more preferably 2 mm or less, particularly preferably 1.5 mm or less), when the power generation element described later is manufactured, the porous metal substrate is compressed in the thickness direction, and its thickness becomes a value described later.
[0101] In order to easily fill the pores of the porous metal substrate with the negative electrode mixture and easily integrate the porous metal substrate with the negative electrode mixture layer in the process of pressurizing the porous metal substrate and the negative electrode mixture, the porosity of the porous metal substrate before being compressed is preferably 80% or more, more preferably 90% or more, and particularly preferably 95% or more. On the other hand, in order to increase the conductivity by making the amount of the substrate above a certain level, the porosity is preferably 99.5% or less, more preferably 99% or less, and particularly preferably 98.5% or less.
[0102] In the negative electrode, from the viewpoint of more reliably integrating the porous metal substrate and the negative electrode mixture layer, the thickness of the portion of the porous metal substrate buried in the negative electrode mixture layer is preferably greater than 10% of the thickness of the porous metal substrate (the thickness of the entire porous metal substrate, including the thickness of the portion where the negative electrode mixture layer coexists; unless otherwise specified, the thickness of the porous metal substrate shall apply the same below), and more preferably greater than 20%.
[0103] In addition, in the negative electrode, in order to reduce the resistance when contacting with the collector used to connect the negative electrodes of multiple power generation elements to each other, it is preferred that the end of the porous metal substrate on the opposite side of the negative electrode mixture layer is not buried in the negative electrode mixture layer, and the end of the negative electrode (the surface of the negative electrode) is only composed of the porous metal substrate. That is, when the porous metal substrate is compressed in the thickness direction during the manufacture of the power generation element described later, it is preferred that the pores at the end of the porous metal substrate are flattened and disappear, and only the porous metal substrate is exposed on the surface of the negative electrode. However, a part of the pores at the end of the porous metal substrate may not be flattened and may be filled with a negative electrode mixture, or a part of the negative electrode mixture may be exposed on the surface of the negative electrode together with the end of the porous metal substrate within a range that does not have a significant impact on the contact resistance with the above-mentioned collector.
[0104] However, the larger the proportion of the negative electrode mixture exposed on the surface of the negative electrode (area ratio), the greater the contact resistance between the porous metal substrate and the collector used to connect the negative electrodes of multiple power generation elements to each other. Therefore, the proportion of the area of the exposed negative electrode mixture in the negative electrode surface is preferably less than 50% when viewed from above, more preferably less than 25%, further preferably less than 15%, and particularly preferably less than 10%.
[0105] In the negative electrode, when at least a portion of the porous metal substrate is buried in the surface layer of the negative electrode mixture layer, from the viewpoint of more reliably integrating the porous metal substrate and the negative electrode mixture layer, the thickness of the porous metal substrate is preferably 1% or more of the thickness of the entire negative electrode mixture layer (including the thickness of the portion coexisting with the porous metal substrate, unless otherwise specified, the "thickness of the negative electrode mixture layer" referred to below refers to the "thickness of the entire negative electrode mixture layer" referred to herein), more preferably 2% or more, and particularly preferably 3% or more. In addition, from the viewpoint of improving the packing property of the negative electrode mixture layer in the negative electrode, the thickness of the porous metal substrate is preferably 30% or less of the thickness of the negative electrode mixture layer, more preferably 20% or less, and particularly preferably 10% or less.
[0106] It should be noted that in the negative electrode, the thickness of the porous metal substrate is preferably 10 μm or more, more preferably 20 μm or more, particularly preferably 30 μm or more, on the other hand, preferably 300 μm or less, more preferably 200 μm or less, particularly preferably 100 μm or less. In addition, the thickness of the negative electrode mixture layer is preferably 0.2 mm or more, more preferably 0.5 mm or more, particularly preferably 0.7 mm or more, on the other hand, preferably 2 mm or less, more preferably 1.7 mm or less, particularly preferably 1.5 mm or less.
[0107] (Solid electrolyte layer)
[0108] In the power generation element, a solid electrolyte layer is placed between the positive electrode and the negative electrode. As a specific example of a solid electrolyte constituting the solid electrolyte layer, the same substance as the solid electrolyte exemplified above as a substance that can be contained in the positive electrode mixture can be cited. Among the solid electrolytes exemplified above, from the perspective of high lithium ion conductivity and the function of improving formability, it is preferred to use a sulfide-based solid electrolyte, and it is more preferred to use a sulfide-based solid electrolyte having a argyrodite-type crystal structure, and it is further preferred to use a solid electrolyte represented by the above-mentioned composition formula (1), the above-mentioned composition formula (2) or the above-mentioned composition formula (3).
[0109] The solid electrolyte layer may have a porous body such as a resin nonwoven fabric as a support.
[0110] The thickness of the solid electrolyte layer is preferably 10 to 200 μm.
[0111] (Shape of power generation element, etc.)
[0112] The shape of the power generating element in a plan view is not particularly limited, and may be any of a circle, an ellipse, a quadrilateral, a hexagon or other polygonal shape, but is usually a circle or a quadrilateral.
[0113] The power generation element may be composed of only a unit stacked electrode body formed by stacking a positive electrode and a negative electrode with a solid electrolyte layer, or may be composed of a plurality of (2, 3, 4, etc.) the above-mentioned unit stacked electrode bodies. There is no particular restriction on the number of unit stacked electrode bodies possessed by the power generation element, and it may be set to 10, 20 or more (usually within about 15). In the case of a power generation element formed by stacking a plurality of unit stacked electrode bodies, the positive electrodes of the unit stacked electrode bodies may be electrically connected to each other by using leads, etc., and the negative electrodes of the unit stacked electrode bodies may be electrically connected to each other by using leads, etc., so that the unit stacked electrode bodies are connected in parallel to each other. In addition, adjacent unit stacked electrode bodies may be stacked in a manner that electrodes with different polarities face each other with a metal foil as a collector, etc., so as to be connected in series. In addition, in the case of a power generation element formed by stacking a plurality of unit stacked electrode bodies, one of the outermost electrodes of the power generation element is a positive electrode, and the other is a negative electrode.
[0114] (Method for manufacturing power generation element)
[0115] The power generating element can be produced, for example, by a production method including the following first to third steps.
[0116] In the first step, the electrode mixture (positive electrode mixture or negative electrode mixture) is put into a mold and pressure-molded. The surface pressure of the pressure-molding in the first step is preferably 30 to 500 MPa, for example.
[0117] In the following second step, a sheet-like conductive substrate is placed on the electrode mixture formed by pressure in the first step, and in the following third step, the electrode mixture and the conductive substrate are pressurized to form an electrode (positive electrode or negative electrode). At this time, when a sheet-like porous metal substrate is used as the conductive substrate, the porous metal substrate is buried in the electrode mixture from the end of the electrode mixture side by the pressurization in the third step, and the electrode mixture is further compressed, and the porous metal substrate is compressed in the thickness direction, so that an electrode (positive electrode or negative electrode) can be formed by integrating the electrode mixture layer (positive electrode mixture layer or negative electrode mixture layer) with the porous metal substrate.
[0118] As described above, when a porous metal substrate is used as a sheet-shaped conductive substrate, in the third step, the porous metal substrate is compressed in the thickness direction, and as the degree of compression, from the viewpoint of more reliably integrating the porous metal substrate and the electrode mixture layer, the thickness of the porous metal substrate after compression is preferably set to 30% or less of the thickness before compression, more preferably to 20% or less, and particularly preferably to 10% or less. In addition, from the viewpoint of maintaining a certain amount of electrode mixture in the voids of the porous metal substrate and improving the bonding strength between the porous metal substrate and the electrode mixture layer, the thickness of the porous metal substrate after compression in the third step is preferably set to 1% or more of the thickness before compression, and more preferably to 2% or more.
[0119] In order to fully improve the density of the electrode mixture layer by compression molding of the electrode mixture, the surface pressure during the pressurization in the third step is, for example, preferably more than 800MPa, more preferably more than 1000MPa, and particularly preferably more than 1200MPa. The upper limit of the surface pressure during the pressurization in the third step is not particularly specified, but in general pressurizing devices, usually about 2000MPa is the upper limit.
[0120] When a porous metal substrate is used as a sheet-shaped conductive substrate, by going through the above-mentioned first step to the above-mentioned third step, an electrode (positive electrode or negative electrode) having the following structure can be obtained: at least a portion of the porous metal substrate including the end on the electrode mixture layer side (a certain range in the thickness direction from the end of the porous metal substrate) is buried in the electrode mixture layer and integrated with the electrode mixture layer, and the other end of the porous metal substrate is exposed on the surface of the electrode.
[0121] It should be noted that if the surface pressure during pressurization in the third step becomes high, cracks may occur when the porous metal substrate is compressed. However, even if it is cut and fragmented, as long as its end is exposed on the surface of the electrode, it can help reduce the contact resistance.
[0122] The positive electrode and the negative electrode can be manufactured through the first step, the second step, and the third step, and these can be arranged on both sides of the solid electrolyte layer and pressed as necessary to form a power generating element.
[0123] Furthermore, before the first step, a preparatory step is provided for placing a solid electrolyte into a mold for pressure molding. In this preparatory step, an electrode mixture (positive electrode mixture or negative electrode mixture) is placed on the pressure-molded solid electrolyte. Then, the first step, the second step and the third step are sequentially performed to produce an integrated product of a solid electrolyte layer and an electrode (positive electrode or negative electrode), which can also be used for power generation elements.
[0124] The surface pressure during the press molding in the preliminary step is preferably set to 30 to 120 MPa, for example.
[0125] Alternatively, a power generating element may be manufactured by forming one of the positive and negative electrodes on a single surface of a solid electrolyte layer through a preparatory step, a first step, a second step, and a third step, and further sequentially performing the first step, a second step, and a third step on the other surface of the solid electrolyte layer to form the other electrode (negative electrode or positive electrode).
[0126] (Configuration and number of power generation elements)
[0127] Figure 6 A perspective view schematically showing an example of a flexible battery is shown. Figure 6 In FIG. 1 , in order to explain the arrangement of the power generating element 110 inside the flexible battery 103 , each power generating element 110 and a portion of the lower substrate and the connection terminal 190 constituting the outer casing 150 are indicated by dotted lines. Figure 6 In the flexible battery 103 shown, nine power generation elements 110 are arranged in three vertical rows and three horizontal rows inside an outer casing 150 .
[0128] In a flexible battery, a plurality of power generating elements may be arranged in a straight line in accordance with the top view shape of the outer casing. Figure 6 As shown, they may be arranged in a plurality of rows in the longitudinal direction and the transverse direction, or in a row in a circle, or in a plurality of rows in a concentric circle.
[0129] The number of power generating elements arranged in the flexible battery is not particularly limited as long as it is multiple, that is, two or more, and can be appropriately selected according to the characteristics required when the battery is used. For example, it can be set to 10, 100, 1000, or more.
[0130] <Flexible substrate, current collector, and outer casing>
[0131] The term "flexible" in the "flexible substrate" used in this specification means that the substrate can be wound around a core having an outer diameter of 3 mm and bent 180 degrees.
[0132] Examples of the flexible substrate for arranging the power generating elements include the above-mentioned flexible sheet-like materials (films, woven fabrics, nonwoven fabrics, etc. having substantially no pores).
[0133] Examples of the raw material of the substrate include resins such as nylon (nylon 66, etc.), polyester [polyethylene terephthalate (PET), etc.], polyolefin (polypropylene, polyethylene, etc.), polyurethane, epoxy, and polyimide.
[0134] The thickness of the substrate is preferably 1 to 100 μm.
[0135] The collector that connects the positive electrodes and negative electrodes of the plurality of power generation elements to each other can be made of metal foil (plate), wire, etc., such as stainless steel, nickel, aluminum, iron, copper, a cladding material formed by combining them, and a material subjected to a plating treatment such as nickel, chromium, or nickel-chromium. It should be noted that from the viewpoint of suppressing the reduction in battery characteristics caused by damage to the electrical connection between the positive electrodes and the negative electrodes of the plurality of power generation elements due to damage to the collector when the flexible battery is deformed, it is preferred that the collector be composed of a metal foil (plate).
[0136] The thickness of the current collector composed of a metal foil (plate) is preferably 1 to 100 μm.
[0137] In a flexible battery, a flexible substrate having an insulating layer and a conductive layer may be used, and the conductive layer may function as a current collector for connecting positive electrodes and negative electrodes of a plurality of power generation elements.
[0138] As the insulating layer in the substrate having an insulating layer and a conductive layer, the above-mentioned flexible sheet-like material and the like can be mentioned.
[0139] In addition, examples of the conductive layer in the substrate having the insulating layer and the conductive layer include metal foils that can be used for the above-mentioned current collectors, etc. The thickness of the conductive layer is preferably 1 to 100 μm.
[0140] The thickness of the insulating layer in the substrate having the insulating layer and the conductive layer is preferably set within a range where the conductive layer satisfies the above-mentioned appropriate thickness and the thickness of the entire substrate satisfies the above-mentioned appropriate thickness.
[0141] The outer casing of the flexible battery only needs to be flexible when the battery is manufactured, and examples thereof include an outer casing composed of a resin film, an outer casing composed of a laminated film having a metal layer on the surface of the resin film, and the like. The resin film constituting the outer casing can use a sheet-like material made of a resin that can be used as a flexible substrate, which is the same as a film having substantially no pores. In addition, the laminated film constituting the outer casing can use a laminated film that is the same as a laminated film having an insulating layer and a conductive layer that can be used as a flexible substrate.
[0142] It should be noted that the outer casing may also be formed of a flexible substrate on which the power generating elements are arranged. That is, the outer casing may be formed by bonding and sealing the outer peripheral edges of two substrates on which the power generating elements are arranged.
[0143] The bonding of the substrates for forming the outer casing can be performed by heat fusion bonding via an ionomer resin, etc. As the ionomer resin, for example, "HIMILAN (ethylene-based ionomer resin, trade name)" manufactured by Dow-Mitsui Polychemicals can be used.
[0144] The shape of the outer casing in a plan view is not particularly limited, and may be a polygon such as a quadrilateral, a circle, or the like.
[0145] <Connection terminal>
[0146] The connection terminal for connecting the flexible battery to the application device can be made of metal plates such as stainless steel, nickel, aluminum, iron, copper, cladding materials composed of these materials, and materials plated with nickel, chromium, nickel-chromium, etc. The thickness of the connection terminal is preferably 10 to 300 μm.
[0147] <Insulator>
[0148] As insulators arranged in the area of the flexible substrate where no power generation element is arranged, there can be cited resins such as ionomer resins (for example, the same substances as those exemplified above as substances for bonding substrates to each other for forming an outer casing), polyolefins (polypropylene, polyethylene, etc.), polyurethanes, epoxy resins, polyimide, and the like.
[0149] When an insulator is used, the portion where the insulator is disposed has the same flexibility as the substrate in order to make the battery flexible. From the viewpoint of ensuring good flexibility and insulation, the thickness of the insulator is preferably 10 to 200 μm.
[0150] Example
[0151] Hereinafter, the present invention will be described in detail based on examples. However, the following examples do not limit the present invention.
[0152] (Example 1)
[0153] The average particle size of lithium titanate (Li4Ti5O 12 , negative electrode active material), a sulfide-based solid electrolyte (Li6PS5Cl) with an average particle size of 0.7 μm and graphene (conductive aid) are mixed in a mass ratio of 50:41:9 to prepare a negative electrode mixture.
[0154] In addition, LiCoO2 (positive electrode active material) with an average particle size of 5 μm and a coating layer of LiNbO3 formed on the surface, a sulfide-based solid electrolyte (Li6PS5Cl) with an average particle size of 0.7 μm, and graphene were mixed in a mass ratio of 65:30.7:4.3 to prepare a positive electrode mixture.
[0155] Next, a powder of a sulfide-based solid electrolyte (Li6PS5Cl) with an average particle size of 0.7 μm was placed in a powder molding mold, and a press was used to perform pressure molding at a surface pressure of 70 MPa to form a temporary molding layer of the solid electrolyte layer. Furthermore, the above-mentioned negative electrode mixture was arranged on the upper surface of the temporary molding layer of the solid electrolyte layer, and pressure molding was performed at a surface pressure of 50 MPa to further form a temporary molding layer of the negative electrode on the temporary molding layer of the solid electrolyte layer.
[0156] Next, a foamed metal porous body (thickness: 1.2 mm, porosity: 98%) obtained by cutting a nickel foamed metal porous body [nickel "Celmet" (registered trademark)] manufactured by Sumitomo Electric Industries, Ltd. into 10 mm × 10 mm squares is placed on the temporary molded layer of the negative electrode formed on the temporary molded layer of the solid electrolyte layer, and pressure molding is performed at a surface pressure of 300 MPa to form an integrated product of the solid electrolyte layer and the negative electrode.
[0157] Furthermore, after turning the mold upside down, the positive electrode mixture is arranged on the upper surface of the solid electrolyte layer in the mold (the opposite side of the surface having the negative electrode), and pressure molding is performed at a surface pressure of 50 MPa to form a temporary molded layer of the positive electrode on the solid electrolyte layer.
[0158] Next, a foamed metal porous body obtained by cutting a nickel-made foamed metal porous body identical to the foamed metal porous body used in the negative electrode is placed on the temporary molded layer of the positive electrode formed on the solid electrolyte layer, and is press-molded at a surface pressure of 1400 MPa to obtain a power generation element having a shape of 10 mm×10 mm and a height of 1.4 mm when viewed from above.
[0159] In the obtained power generation element, the thickness of the negative electrode mixture layer of the negative electrode, the thickness of the porous metal substrate, and the thickness of the portion of the porous metal substrate buried in the negative electrode mixture layer were 740 μm, 50 μm (4% of the thickness of the porous metal substrate before being used for the negative electrode), and 10 μm (20% of the total thickness of the porous metal substrate). In addition, the area ratio of the portion of the negative electrode mixture exposed on the surface of the negative electrode was 7%.
[0160] In addition, in the obtained power generation element, the thickness of the positive electrode mixture layer of the positive electrode, the thickness of the porous metal substrate, and the thickness of the portion of the porous metal substrate buried in the positive electrode mixture layer were 420 μm, 50 μm (4% of the thickness of the porous metal substrate before being used for the positive electrode), and 10 μm (20% of the total thickness of the porous metal substrate). In addition, the area ratio of the portion of the positive electrode mixture exposed on the surface of the positive electrode was 7%.
[0161] Prepare two laminated films having an insulating layer made of nylon 66 and a conductive layer made of stainless steel foil and having a size of 60 mm×60 mm (the thickness of the insulating layer is 45 μm, and the thickness of the conductive layer is 40 μm), and install nickel connecting terminals (3 mm×15 mm, thickness of 50 μm) in each of them.
[0162] Then, on the conductive layer of one side of the laminated film, the 9 power generation elements obtained as described above were arranged in 3 vertical rows and 3 horizontal rows with a spacing of 10 mm between the power generation elements, and an ionomer resin ["HIMILAN (trade name)" manufactured by Dow Mitsui Polychemicals Co., Ltd.] was arranged in a thickness of 0.1 mm in the area where no power generation elements were arranged.
[0163] Then, the conductive layer is placed on the power generation element side to cover the remaining laminate film, and the whole is heat-pressed to fuse the ionomer resin to the upper and lower laminate films. The outer peripheral ends of the four sides are further sealed by heat-pressing to obtain a flexible battery.
[0164] (Reference example)
[0165] On both sides of the positive and negative sides of the power generation element prepared in the same manner as in Example 1, nickel leads with a thickness of 50 mm were resistance welded, and the leads were sandwiched in a laminated film consisting of a three-layer structure of nylon / aluminum / CPP (unstretched polypropylene) (each with a thickness of 25 μm / 40 μm / 40 μm) in a form in which the leads protruded from the laminated film, and the outer peripheral ends of the four sides of the laminated film were sealed by heat pressing to prepare a fully solid-state battery. Instead of the power generation element, these fully solid-state batteries were arranged in a manner so that the leads were in contact with the conductive layer of the outer casing, and a flexible battery was prepared in the same manner as in Example 1 except that the flexible battery was prepared.
[0166] (Comparative Example 1)
[0167] A flexible battery was produced in the same manner as in Example 1 except that a power generating element having a height of 1.3 mm was used in which the nickel-made foamed metal porous body was not disposed on the surfaces of the positive electrode and the negative electrode.
[0168] The flexible batteries of Examples, Reference Examples, and Comparative Examples were subjected to the following evaluations.
[0169] (0.2C discharge capacity)
[0170] For each flexible battery of the embodiment, reference example and comparative example, in the unfolded state, 90 mA was used as the current value equivalent to 1C, and constant current charging was performed at a current value equivalent to 0.5C until the voltage reached 2.6V, and then constant voltage charging was performed at a voltage of 2.6V until the current value reached 0.01C, and then constant current discharge was performed at a current value equivalent to 0.2C until the voltage reached 1.0V. The discharge capacity at this time was taken as the 0.2C discharge capacity of each flexible battery.
[0171] (0.5C discharge capacity)
[0172] Each flexible battery having a measured 0.2C discharge capacity was charged in the same manner as above and then discharged at a constant current value corresponding to 0.5C until the voltage reached 1.0 V. The discharge capacity at this time was defined as the 0.5C discharge capacity of each flexible battery.
[0173] Next, each flexible battery of the embodiment, reference example and comparative example was folded twice in the longitudinal direction at the portion where the power generating element was not arranged, to form a Figure 4 The 0.2C discharge capacity and the 0.5C discharge capacity in the folded state and the 0.5C discharge capacity in the folded state are measured in the same manner as above, and are referred to as the 0.2C discharge capacity in the folded state and the 0.5C discharge capacity in the folded state, respectively.
[0174] (Evaluation of energy density)
[0175] When each flexible battery of the embodiment, reference example and comparative example was folded twice as described above, the maximum lengths of the sides were multiplied to obtain the maximum volume of each flexible battery. The energy density (volume energy density) of each flexible battery was calculated by dividing the value obtained by multiplying the 0.2C discharge capacity in the folded state by the average operating voltage during the discharge by the maximum volume obtained as described above.
[0176] The above discharge capacity results for each flexible battery of Example, Reference Example and Comparative Example are shown in Table 1. It should be noted that each value in Table 1 is a relative value when the 0.2C discharge capacity obtained when the flexible battery of Example 1 is unfolded is set to 100.
[0177] [Table 1]
[0178]
[0179] In addition, for each flexible battery of the example and the comparative example, the energy density was calculated as shown in Table 2. It should be noted that each value in Table 2 is a relative value when the value of the flexible battery of Example 1 is set to 100.
[0180] [Table 2]
[0181] Maximum volume Energy density Example 1 100 100 Reference example 113 88 Comparative Example 1 94 102
[0182] As shown in Table 1, the flexible batteries of Example 1 and Reference Example can be Figure 4 In the folded state, the battery can be charged and discharged in the same manner as in the unfolded state, and the capacity reduction is less than 3%. Therefore, it can be said that the flexible battery of Example 1 can reduce the internal resistance to the same level as the flexible battery of the reference example in which the power generation elements are externally mounted and connected to each other, although the positive electrodes are directly connected to each other through the current collector, and the negative electrodes are directly connected to each other through the current collector.
[0183] On the other hand, in the flexible battery of Comparative Example 1, in which each power generation element is not separately externally mounted and a sheet-like conductive substrate (foamed metal porous body) is not arranged on the surface of the positive electrode mixture layer and the negative electrode mixture layer of each power generation element, the obtained discharge capacity is smaller than that of the flexible battery of Example 1, especially when the discharge current is high. Therefore, it can be said that the flexible battery of Comparative Example 1 has a larger internal resistance than the flexible battery of Example 1.
[0184] In addition, it can be seen from Table 2 that compared with the flexible battery in which the power generation elements are wrapped with an outer packaging body and arranged as a reference example of an all-solid-state battery, Example 1, in which the power generation elements are not externally packaged, their positive electrodes are directly connected to each other through collectors, and their negative electrodes are directly connected to each other through collectors, can improve the energy density.
[0185] The present invention can also be implemented in a manner other than the above without departing from its purport. The embodiments disclosed in this application are examples, and the present invention is not limited to these embodiments. The scope of the present invention is interpreted preferentially in accordance with the appended claims compared to the description of the above specification, and all changes within the scope equivalent to the claims are included in the claims.
[0186] Industrial Applicability
[0187] The flexible battery of the present invention can be used in the same applications as conventionally known primary batteries and secondary batteries, but because it has a solid electrolyte instead of an organic electrolyte, it has excellent heat resistance and can be preferably used in applications exposed to high temperatures.
[0188] Explanation of symbols
[0189] 100, 101, 102, 103 Flexible batteries
[0190] 110 Power generation element
[0191] 120 Positive electrode
[0192] 121 positive electrode mixture layer
[0193] 121a Positive electrode mixture
[0194] 122 Sheet-shaped porous metal substrate (sheet-shaped conductive substrate)
[0195] 130 Negative electrode
[0196] 131 Negative electrode mixture layer
[0197] 132 Sheet-shaped porous metal substrate (sheet-shaped conductive substrate)
[0198] 140 Solid electrolyte layer
[0199] 150 outer body
[0200] 160, 170 Flexible substrate
[0201] 161, 171 insulation layer
[0202] 162, 172 conductive layer (current collector)
[0203] 180, 190 connection terminals
[0204] 200 Insulator.
Claims
1. A flexible battery comprising a plurality of power generation elements enclosed in an outer casing, characterized in that: The power generation element includes a positive electrode, a negative electrode, and a solid electrolyte layer disposed between the positive electrode and the negative electrode. The positive electrode comprises a positive electrode mixture layer and a sheet-like conductive substrate disposed on a surface of the positive electrode mixture layer. The negative electrode comprises a negative electrode mixture layer and a sheet-like conductive substrate disposed on a surface of the negative electrode mixture layer. The plurality of power generating elements are arranged on a flexible substrate, and each positive electrode is directly connected to a current collector so that the positive electrodes are connected to each other through the current collector, and each negative electrode is directly connected to a current collector so that the negative electrodes are directly connected to each other through the current collector. The current collectors connecting the positive electrodes to each other and the current collectors connecting the negative electrodes to each other are connected to connection terminals leading to the outside, respectively.
2. The flexible battery according to claim 1, wherein: The conductive substrate of the positive electrode is a porous metal substrate, at least a portion of which, including an end portion on the positive electrode mixture layer side, is buried in the surface layer of the positive electrode mixture layer and integrated with the positive electrode mixture layer, and the other end portion of the porous metal substrate of the positive electrode is exposed on the surface of the positive electrode. The conductive substrate of the negative electrode is a porous metal substrate, at least a portion of which, including the end portion on the negative electrode mixture layer side, is buried in the surface portion of the negative electrode mixture layer and integrated with the negative electrode mixture layer, and the other end portion of the porous metal substrate of the negative electrode is exposed on the surface of the negative electrode.
3. The flexible battery according to claim 1, wherein: The flexible substrate has an insulating layer and a conductive layer. The conductive layer functions as the current collector.
4. The flexible battery according to claim 1, wherein: The outer casing is composed of the flexible base material.
5. The flexible battery according to claim 1, wherein: An insulator is disposed in at least a portion of a region of the flexible substrate where the power generating element is not disposed.
Citation Information
Patent Citations
Sheet-shaped battery
JP2000195482A
Flexible battery and electronic apparatus
JP2015015143A
Foldable battery module
WO2016092888A1
Halide solid electrolyte material and battery using same
WO2020070955A1
Halide solid electrolyte material and battery using same
WO2020070958A1